The Value Of Noble Character Education For Javanese Society In The Trilogy Novel “Gadis Tangsi” By Suparto Brata - Sutardi Sutardi; Sariban Sariban; Hendrik Furqon (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study addresses the limited scholarly attention to Suparto Brata’s Gadis Tangsi trilogy as a literary source for understanding noble character values in Javanese society. It aims to identify and interpret the forms of character education represented in the trilogy and to explain their relevance to readers within a pragmatic literary perspective. The study employed a descriptive qualitative design. Data were drawn from the three novels in the Gadis Tangsi trilogy and were supported by documentation and interviews. The data were analyzed through an interactive model involving data reduction, data display, interpretation, and conclusion drawing, while validity was strengthened through triangulation of theory, data, and methods. The findings show that the trilogy presents character education as an integrated moral-cultural framework rather than as isolated lessons. The narrative consistently portrays the virtues expected of Javanese women, a disciplined work ethic, ethical conduct in social relations, spiritual awareness, and broader ideals of personal character. These values are embedded in the characters’ actions, conflicts, and choices, revealing how social responsibility, self-control, dignity, and inner balance are cultivated within Javanese cultural life. The novelty of this study lies in its synthesized reading of the trilogy as a coherent representation of noble character formation in Javanese society. This contribution enriches literary studies by demonstrating how narrative fiction preserves cultural ethics and transmits social ideals across generations. It also offers a relevant model for character education by showing that literary texts can function as reflective pedagogical resources in contemporary learning contexts for schools and universities today.